Renewable energy, trade diversification and environmental footprints: Evidence for Asia-Pacific Economic Cooperation (APEC) - Jiang, Shaohua; Mentel, Grzegorz; Shahzadi, Irum [UNESP]; Ben Jebli, Mehdi; Iqbal, Najaf (Elsevier, 2022)
The prime objective of this research is to explore the impacts of import and export diversification and renewable energy on environmental footprints. In doing so, the authors employ the data of trade diversification, income inequality, renewable energy, and ecological footprints for 17 Asia-Pacific Economic Cooperation (APEC) countries covering the period of 1995–2019. In econometric framework, the authors use two baseline empirical models based on key indicators such as trade (exports and imports) diversification index, income inequality, renewable energy, and globalization. The empirical analysis from both specifications suggests a cointegrating relation between the key variables of interest. The Long-run empirical estimates from FMOLS, and DOLS methods indicate that income inequality and import diversification increase ecological issues while globalization and exports diversification abate it. Further analysis through Granger causality highlights unilateral causal relationships running from renewable energy consumption to imports diversification, and from ecological footprint to imports diversification. The conclusions of this study stress the importance of harmonic policies, synchronization in trade, energy and resource consumption in achieving sustainable development goals.
Keywords: APEC countries; Environmental footprints; Income quality; Product diversification; Renewable energy; Sustainable development